Lignicolous freshwater fungi from China II: Novel Distoseptispora (Distoseptisporaceae) species from northwestern Yunnan Province and a suggested unified method for studying lignicolous freshwater fungi - Z. L. Luo (2018)
© Guizhou Academy of Agricultural Sciences. This is the second in a series of papers on lignicolous freshwater fungi from China. In this paper, eight fresh collections of asexual morphs of Distoseptispora, isolated from submerged wood in northwestern Yunnan Province, China, are characterized based on morphological characters and phylogenetic analyses of combined ITS, LSU, RPB2 and TEF1α sequence data. Four new Distoseptispora species (D. cangshanensis, D. obpyriformis, D. rostrata and D. submersa) are introduced, described and illustrated, with notes on their taxonomy and phylogeny. Newly generated molecular data of Distoseptispora fluminicola is also provided. We also provide a unified method for studying lignicolous freshwater fungi to standardize the findings of future Asian studies.